Antifungal activity of polymethyl methacrylate/Si3N4 composites against Candida albicans. (May 2021) - Pezzotti, Giuseppe; Asai, Tenma; Adachi, Tetsuya; Ohgitani, Eriko; Yamamoto, Toshiro; Kanamura, Narisato; Boschetto, Francesco; Zhu, Wenliang; Zanocco, Matteo; Marin, Elia; Bal, B. Sonny; McEntire, Bryan J.; et al.
Abstract: Previous studies using gram-positive and -negative bacteria demonstrated that hydrolysis of silicon nitride (Si3 N4 ) in aqueous suspensions elutes nitrogen and produces gaseous ammonia while buffering pH. According to immunochemistry assays, fluorescence imaging, and in situ Raman spectroscopy, we demonstrate here that the antipathogenic surface chemistry of Si3 N4 can be extended to polymethylmethacrylate (PMMA) by compounding it with a minor fraction (~8 vol.%) of Si3 N4 particles without any tangible loss in bulk properties. The hydrolytic products, which were eluted from partly exposed Si3 N4 particles at the composite surface, exhibited fungicidal action against Candida albicans . Using a specific nitrative stress sensing dye and highly resolved fluorescence micrographs, we observed in situ congestion of peroxynitrite (ONOO − ) radicals in the mitochondria of the Candida cells exposed to the PMMA/Si3 N4 composite, while these radicals were absent in the mitochondria of identical cells exposed to monolithic PMMA. These in situ observations suggest that the surface chemistry of Si3 N4 mimics the antifungal activity of macrophages, which concurrently produce NO radicals and superoxide anions (O2 − ) resulting in the formation of candidacidal ONOO − . The fungicidal properties of PMMA/Si3 N4 composites could be used in dental appliances to inhibit the uncontrolled growth of Candida albicans and ensuing candidiasis while being synergic with chemoprophylaxis. Statement of significance: In a follow-up of previous studies of gram-positive and gram-negative bacteria, we demonstrate here that the antipathogenic surface chemistry of Si3 N4 could be extended to polymethylmethacrylate (PMMA) containing a minor fraction (~8 vol.%) of Si3 N4 particles without tangible loss in bulk properties. Hydrolytic products eluted from Si3 N4 particles at the composite surface exhibited fungicidal action against Candida albicans . Highly resolved fluorescence microscopy revealed congestion of peroxynitrite (ONOO − ) radicals in the mitochondria of the Candida cells exposed to the PMMA/Si3 N4 composite, while radicals were absent in the mitochondria of identical cells exposed to monolithic PMMA. The fungicidal properties of PMMA/Si3 N4 composites could be used in dental appliances to inhibit uncontrolled growth of Candida albicans and ensuing candidiasis in synergy with chemoprophylaxis. GraphicaI abstract: Image, graphical abstract